Wind-induced equivalent static interference criteria and its effects on cooling towers with complex arrangements. (1st October 2018) - Zhao, Lin; Zhan, Yanyan; Ge, Yaojun
Highlights: Wind tunnel tests on complex-grouped super-large cooling towers were performed. Wind tunnel tests, FEM and reinforcement design were integrated in the process. Interference Factors ( IF s) for various definition criteria are compared in both value and volatility. Adverse interference conditions for two arrangements are analyzed based on IF s. Multiple IF s along shell height are proposed based on reinforcement envelopes. Abstract: Wind-induced interference is a controlling factor in the design of grouped cooling towers. To meet structural safety requirements, interference factor ( IF ) is commonly used to envelope the multiple complex static wind pressure distributions caused by it. However, the parameter turns out to be quite scattered for different evaluation criteria. To compare those criteria and study tower-group interference effects among complex arrangements, cooling tower groups with typical six-tower double-column arrangements were selected to perform wind tunnel tests and FEM calculation. Interference effects among classical rectangular and rhombic combinations were investigated, considering several typical center-to-center distances between towers. Wind pressure under 15 × 16 incoming flow conditions for 1:200 reduced-scale models was measured and corresponding 3-D quasi-static and static calculations were carried out to analyze the IF s. Totally, twenty-five kinds of IF s were compared based on criteria at three aspects: aerodynamic loading, structure response and reinforcement ratio. Some principal conclusions are synthesized as follows: the values of IF s for twenty-five criteria are quite different even for a same tower and their fluctuation under different cases is not the same as well, but those criteria are in accordance with each other in reflecting adverse interference conditions; the unified IF widely applied by loading codes cannot economically cover complex spatial wind pressure distributions caused by interference effects; multiple factors changing along the tower shell are recommended as a possible alternative, taking into account convenience, economy and rationality.